A university‐led initiative to expand pharmacy residency program development statewide. Issue 3 (4th October 2022) - Taylor, Stacy; Hudspeth, Brooke
Abstract: Given trends in pharmacy practice advancement, additional residency training positions are needed to meet future workforce development goals. Although there has been aggressive growth in the number of pharmacy residency training programs over the past decade, a shortage in the number of available residency positions persists. As such, residency expansion initiatives across the profession are ongoing. To describe a university‐led initiative to expand pharmacy residency program development statewide, programmatic outcomes associated with implementation, and key elements of success. Health systems interested in residency program development were invited to participate in a university‐led initiative that included an online residency resource repository, preceptor interest inventory, monthly video calls, collaboratively established goals and deadlines, and preceptor development. Health system participation rates, utilization of resources, and programmatic outcomes such as number of new residency programs and positions were tracked over time. Over a 3‐year period, six health systems participated in the initiative, yielding four new postgraduate year 1 (PGY1) programs and eight new PGY1 positions. Five of six health systems utilized the online resources and participated in the monthly video calls. Four of the six health systems accessed the preceptor development materials. A University‐led initiative is an effective method for developing new residency training programs. Widescale efforts to implement models such as this one, could prove beneficial in addressing the nationwide shortage of residency programs.